HIV Infections Among Older Male Clients of Low-Cost Commercial Sex Venues in Southern China. Issue 1 (2nd January 2017) - Wu, Xinghua; Feng, Xue; Kelly, Carolyn; Shen, Zhiyong; Chen, Huanhuan; Lu, Huaxiang; Luo, Liuhong; Chen, Li; Ruan, Yuhua; Tang, Zhenzhu
ABSTRACT: This study aimed to identify the association of unsafe sex behaviors with HIV infection among the male clients who purchase commercial sex in low-cost sex venues. A cross-sectional study was conduct in a southern province of China among male, low-cost commercial sex clients, who were over 50 years old. Participants were interviewed using a structured questionnaire and had completed HIV testing. Among the 3, 485 participants, the prevalence of HIV was 2.96% (95% confidence interval: 2.40–3.52%). The associated risk factors studied for HIV infection included (1) not currently married; (2) use of counterfeit TCMs with sildenafil; (3) noncondom use during commercial purchased sex; and (4) recent engagement of commercial sex within past week. Given the high prevalence of HIV infection among the study group, more political policy intervention and health education should be considered for the identified subpopulation (over 50-year-old men in low-cost commercial venues, counterfeit TCMs with sildenafil and noncondom use).